CAKUNG - PERTANIAN RAMAH LINGKUNGAN DIKAWASAN PERKOTAAN - Joshua Keeve Tandra; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2021)
In 2020, mankind throughout the world will be shaken by the Covid-19 which greatly affected people's lives and caused a lot of unrest. The Indonesian government implements a